(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the importance and application of innovative educational technologies in teaching literature. The study is aimed at studying the level of use of innovative educational technologies by teachers of literature in Uzbekistan. The article presents the results obtained based on literature analysis, conducting surveys and observations. The data obtained show that literature teachers are interested in applying innovative educational technologies, but there are some obstacles to their implementation in practice. The conclusion provides recommendations for the effective introduction of innovative educational technologies.